Identification of fields of action for validation in Systems Engineering - Humpert, Lynn; Zagatta, Kristin; Anacker, Harald; Dumitrescu, Roman (IEEE International Conference on Technology Management, Operations and Decisions (IEEE ICTMOD))

Strategic planning of the collaboration between humans and artificial intelligence in production - Gabriel, Stefan; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Principles for the effective application of Systems Engineering: A systematic literature review and application use case - Mundt, Enrik; Wilke, Daria; Anacker, Harald; Dumitrescu, Roman

Integration von Design Thinking in Systems Engineering mit Hilfe des Systemdenkens - Tekaat, Julian; Wilke, Daria; Anacker, Harald; Dumitrescu, Roman

Lydia Böttger (Universität Paderborn) rezensiert: Burwitz-Melzer, Eva; Riemer, Claudia; Schmelter, Lars (Hrsg.) (2022): Feedback beim Lehren und Lernen von Fremd- und Zweitsprachen. Arbeitspapiere der 42. Frühjahrs- konferenz zur Erforschung des Fremdsprachenunterrichts. [Giessener Beiträge zur Fremdsprachendidaktik]. Tübingen: Narr Francke Attempto, 245 Seiten. ISBN 978-3- 8233-8569-1 - Böttger, Lydia (www.daz-portal.de)

Alignment between timing of ‘highest caloric intake’ and chronotype in relation to body composition during adolescence: the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Stutz, Bianca; Krüger, Bettina; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose Our aim was to assess alignment in timing of ‘highest caloric intake’ with individual chronotype and its association with body composition in adolescents. Methods We used repeatedly collected data from n = 196 adolescents (age 9–16 years, providing N = 401 yearly questionnaires) of the DONALD open cohort study. Chronotype was assessed by the Munich Chronotype Questionnaire from which midpoint of sleep (MSFsc) was derived. A sex- and age-specific diet-chrono-alignment score (DCAS) was calculated as the difference in hours between the chronotype-specific median timing of highest caloric intake of the studied population and the individual timing of ‘highest caloric intake’ or vice versa. Repeated-measures regression models were applied to study cross-sectional and longitudinal associations between the DCAS and body composition, e.g., Fat Mass Index (FMI) or Fat Free Mass Index (FFMI). Results DCAS ranged from −6:42 h to + 8:01 h and was not associated with body composition. Among adolescents with a later chronotype ( N = 201) a 1 h increase in DCAS (later consumption of ‘highest caloric intake’ in comparison to the median intake of that group), increased FFMI by 1.92 kg/m 2 (95% CI: 0.15, 3.69, p value = 0.04) over a median follow-up of 0.94 year. Conclusion Alignment of energy intake with individual chronotype appears beneficial for FFMI among those with a late chronotype.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Re-examining the quality dimensions of synthetic speech - Seebauer, Fritz; Kuhlmann, Michael; Haeb-Umbach, Reinhold; Wagner, Petra (12th Speech Synthesis Workshop (SSW) 2023)

Professionelle Unterrichtswahrnehmung von Lehramtsstudierenden – das Projekt iDEAL. Vortrag auf der Herbsttagung 2023 der Arbeitsgruppe Empirische Sonderpädagogische Forschung (AESF) - Görel, Gamze; Finke, Pauline; Hellmich, Frank

Breaking Down Barriers: How Conversational Agents Facilitate Open Science and Data Sharing - Mirbabaie, Milad; Rieskamp, Jonas; Hofeditz, Lennart; Stieglitz, Stefan

From Virality to Veracity: Examining False Information on Telegram vs. Twitter - Rieskamp, Jonas; Mirbabaie, Milad; Langer, Marie; Kocur, Alexander

Accelerating the analysis of optical quantum systems using the Koopman operator - Peitz, Sebastian; Hunstig, Anna; Rose, Hendrik; Meier, Torsten
The prediction of photon echoes is an important technique for gaining an understanding of optical quantum systems. However, this requires a large number of simulations with varying parameters and/or input pulses, which renders numerical studies expensive. This article investigates how we can use data-driven surrogate models based on the Koopman operator to accelerate this process. In order to be successful, we require a model that is accurate over a large number of time steps. To this end, we employ a bilinear Koopman model using extended dynamic mode decomposition and simulate the optical Bloch equations for an ensemble of inhomogeneously broadened two-level systems. Such systems are well suited to describe the excitation of excitonic resonances in semiconductor nanostructures, for example, ensembles of semiconductor quantum dots. We perform a detailed study on the required number of system simulations such that the resulting data-driven Koopman model is sufficiently accurate for a wide range of parameter settings. We analyze the L2 error and the relative error of the photon echo peak and investigate how the control positions relate to the stabilization. After proper training, the dynamics of the quantum ensemble can be predicted accurately and numerically very efficiently by our methods.

An IAD framework analysis of minigrid institutions for sustainable rural electrification in East Africa: A comparative study of Uganda and Tanzania - Namujju, Lillian Donna; Acquah-Swanzy, Henrietta; Ngoti, Irene F. (Energy Policy)
Keywords: Management; Monitoring; Policy and Law; General Energy

Sure you are ready? Gendered arguments in recruitment for high-status positions in male-dominated fields - Dutz, Regina; Hubner-Benz, Sylvia; Emmerling, Franziska; Peus, Claudia (Frontiers in Psychology)
Recruitment contexts such as STEM professorships promote clearly defined selection criteria and objective assessment. We illuminate in these contexts, the subjective interpretation of seemingly objective criteria and gendered arguments in discussions of applicants. Additionally, we explore gender bias despite comparable applicant profiles investigating how specific success factors lead to selection recommendations for male and female applicants. Implementing a mixed methods approach, we aim to highlight the influence of heuristics, stereotyping, and signaling in applicant assessments. We interviewed 45 STEM professors. They answered qualitative open-ended interview questions, and evaluated hypothetical applicant profiles, qualitatively and quantitatively. The applicant profiles enabled a conjoint experiment with different applicant attributes varied across the profiles (i.e., publications, willingness to cooperate, network recommendation, and applicant gender), the interviewees indicating scores of selection recommendation while thinking aloud. Our findings reveal gendered arguments, i.e., questioning women potentially fueled by a perception of women’s exceptional status and perceived self-questioning of women. Furthermore, they point to gender-independent and gender-dependent success patterns, thereby to potential success factors particularly for female applicants. We contextualize and interpret our quantitative findings in light of professors’ qualitative statements.
Keywords: General Psychology

Robot leadership–Investigating human perceptions and reactions towards social robots showing leadership behaviors - Cichor, Jakub Edward; Hubner-Benz, Sylvia; Benz, Tobias; Emmerling, Franziska; Peus, Claudia (PLOS ONE)
Human-robot interaction research has shown that social robots can interact with humans in complex social situations and display leadership-related behaviors. Therefore, social robots could be able to take on leadership roles. The aim of our study was to investigate human followers’ perceptions and reactions towards robot leadership behavior, and differences based on the robot’s displayed leadership style. We implemented a robot to show either a transformational or a transactional leadership style in its speech and its movements. We presented the robot to university and executive MBA students (N = 29) and subsequently conducted semi-structured interviews and group discussions. The results of explorative coding indicated that participants differed in their perceptions and reactions based on the robot’s leadership style and based on their assumptions about robots in general. We observed that participants quickly imagined either a utopia or worried about a dystopia, depending on the robot’s leadership style and their assumptions, and that a subsequent reflection led to more nuanced views. We discuss the implications and recommendations for human-robot interaction and leadership research.
Keywords: Multidisciplinary

What predicts effectuation preferences Disentangling individual and environmental factors and illuminating decision criteria - Hubner-Benz, Sylvia; Baum, Matthias (International Journal of Entrepreneurial Venturing)
Keywords: Management of Technology and Innovation; Strategy and Management; Business and International Management

Different ways lead to ambidexterity: Configurations for team innovation across China, India, and Singapore - Deng, Wei; Hubner-Benz, Sylvia; Frese, Michael; Song, Zhaoli (Journal of International Management)
Keywords: Strategy and Management; Finance; Business and International Management

Ambivalenzkompetenz? Rückblick auf die Tagung "Katastrophen". Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert am Vortag des russischen Angriffs auf die Ukraine - Schroeter-Wittke, Harald; Breckner, Anne (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Combined Economic and Emission Dispatch of a Microgrid Considering Multiple Generators - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Proceedings of the 2023 IEEE PES/IAS PowerAfrica Conference)

Demand side management potential of refrigeration appliances - Kakande, Josephine Nakato; Philipo, Godiana Hagile; Krauter, Stefan (Proceedings of the 2023 IEEE PES/IAS PowerAfrica Conference)

Demand-Side-Management for Optimal dispatch of an Isolated Solar Microgrid - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Proceedings of the 2023 IEEE AFRICON, Nairobi, Kenya)